Health Risks from Intake and Contact with Toxic Metal-Contaminated Water from Pager River, Uganda - Patrick Onen; Robin Akemkwene; Caroline K. Nakiguli; Daniel Nimusiima; Daniel Hendry Ruma; Alice V. Khanakwa; Christopher Angiro; Gadson Bamanya; Boniface Opio; Allan Gonzaga; Timothy Omara (MDPI AG, 2023)
Pollution of water resources is one of the major impediments to the realization of Sustainable Development Goals, especially in developing countries. The aim of this study was to investigate the physicochemical quality and potentially toxic element (lead and cadmium) concentrations in surface water sampled from Pager River, a tributary of the Nile River in Northern Uganda. Water samples (n = 18) were taken from six different points upstream (A, B, and C) and downstream (D, E, and F) of the river and analyzed following standard methods for their physiochemical properties. Atomic absorption spectroscopy was used to quantify lead and cadmium concentrations. Human health risks from ingestion and dermal contact with potentially toxic metal-contaminated water were calculated. The results obtained indicated that the mean temperature (27.7 ± 0.5-29.5 ± 0.8 °C), turbidity (40.7 ± 2.1-50.1 ± 1.1 NTU), lead (0.296 ± 0.030-0.576 ± 0.163 mg/L) and cadmium (0.278 ± 0.040-0.524 ± 0.040 mg/L) occurred at levels that surpassed their permissible limits as per World Health Organization guidelines for drinking water. Human health risk assessment showed that there are potential non-cancer risks from the ingestion of water from Pager River by adults, as the total hazard quotients were greater than one. These results emphasize the urgency to restrict the dumping of wastes into the river to minimize chances of impacting the Nile River, which flows northwards to the Mediterranean Sea. Further studies should perform routine monitoring of the river during both dry and wet seasons to establish the spatiotemporal variations of physicochemical, microbial, and trace metal profiles of the river and the associated health risks.